Occurrence and risk assessment of organophosphate esters in drinking water from Eastern China - Ding, Jinjian; Shen, Xiaoli; Liu, Weiping; Covaci, Adrian; Yang, Fangxing (The Science of the total environment, 2015)
Organophosphate esters (OPEs) are ubiquitous in the environment and may pose potential health risks to humans. Drinking water is suspected as one possible exposure pathway of OPEs to humans. In this study, we investigated the residues of 9 OPEs in five types of drinking water in Eastern China. The median concentrations of Σ9OPEs were determined to be 3.99, 4.50, 27.6, 59.2 and 192ng/L in the bottled, well, barreled, direct drinking and tap waters, respectively. Triethyl phosphate (TEP) was the most abundant OPE in the tap water and filtered drinking water with median concentrations of 50.2 and 30.2ng/L, respectively. The mixture of tri(chloropropyl) phosphate (TCPP) and tri(chloroisopropyl) phosphate (TCIPP), named here as TCPP, dominated in the barreled and well water with median concentrations of 8.04 and 2.49ng/L, respectively. The calculated average daily doses of OPEs ranged from 0.14 to 7.07ng/kgbw/day for people consuming the five different types of drinking water. Among the drinking water, the tap water exhibited the highest exposure doses of OPEs. The calculated non-cancer hazard quotients (10−4–10−7) from OPEs were much lower than the theoretical threshold of risk. The carcinogenic risks posed by TCEP were very low (<10−7) for all types of drinking water. The results revealed that there was currently low risk to human health from exposure to OPEs through drinking water in Eastern China. [Display omitted] •Residues of OPEs in drinking water were investigated in Eastern China.•The concentrations of OPEs in tap water were higher than other drinking waters.•Uptake of OPEs via drinking water was similar to airborne exposure for adults.•Non-cancer and carcinogenic risks of OPEs for people via drinking water were low.